Unicondylar knee prosthesis: our experience - Valentini, Roberto; De Fabrizio, Giovanni; Piovan, Gianluca; Stasi, Alessandro (Acta Biomedica Atenei Parmensis, 2014)
Aim of the study. To compare unicompartmental knee arthroplasty with “all poly“ tibial component and “metal back” from a clinical and functional point of view. Materials and methods. We evaluated prospectively 50 patients who underwent unicompartmental knee replacement at the Orthopedic Clinic of the University of Trieste. Patients were split into two groups (A and B); in patients from group A has been implanted a Mitus prosthesis (Link) with “all poly“ tibial component, in patients from Group B has been implanted an Allegretto prosthesis (Zimmer) with a “metal back“ tibial component. The mean follow-up was 36 months. All patients were evaluated using the Knee Society Score. Results. The mean preoperative Knee Society Score (objective and functional) was found to be respectively 48 and 49 or the group A and group B; post-operative score was found to be of 95 and 94 respectively for Group A and group B. The average post-operative ROM was 125 degrees (range, 85-140 degrees) for group A and 130° (range 90°-145°) for group B. Conclusions. No differences were found between implants with “all poly” tibial component (thickness to be used must be greater than 6 mm) and those with the “metal back”. We believe that to achieve positive results over time is important the carefully selection of the patients and the accurate positioning of components.